Βιβλιογραφικό σημείωμα: Storytelling in Byzantium : narratological approaches to Byzantine texts and images / edited by Charis Messis, Margaret Mullett & Ingela Nilsson, Uppsala 2018, σελ. X+320. ISBN 978-91-513-0362-8 - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2021)
Βιβλιογραφικό σημείωμα: Storytelling in Byzantium : narratological approaches to Byzantine texts and images / edited by Charis Messis, Margaret Mullett & Ingela Nilsson, Uppsala 2018, σελ. X+320. ISBN 978-91-513-0362-8